Naloxone Ameliorates Spatial Memory Deficits and Hyperthermia Induced by a Neurotoxic Methamphetamine Regimen in Male Rats: - Ghazvini, Hamed; Khalifeh, Solmaz; Khodamoradi, Mehdi; Hajali, Vahid; Eliasy, Lelia; Kheradmand, Afshin; Farnia, Vahid; Akhtari, Javad; Shahveisi, Kaveh; Ghalehnoei, Hossein (Galen Medical Journal, 2019)
Background: Methamphetamine (METH) as a synthetic psychostimulant is being increasingly recognized as a worldwide problem, which may induce memory impairment. On the other hand, it is well established that naloxone, an opiate antagonist, has some beneficial effects on learning and memory. The present research aimed at evaluating naloxone effects on spatial learning and memory impairment triggered by a neurotoxic regimen of METH in male rats. Materials and Methods: The animals received the subcutaneous (sc) regimen of METH (4×6 mg/kg at 2-h intervals), intraperitoneal (ip) naloxone (4×1 mg/kg at 2-h intervals), or normal saline at four events. The Nal-METH group of rats received four naloxone injections (1 mg/kg, ip) 30 min before each METH injection (6 mg/kg, sc) at 2-h intervals. Seven days later, they were evaluated for spatial learning and memory in the Morris Water Maze (MWM) task. Result: METH regimen induced hyperthermia, as well as a poor performance, in the acquisition and retention phases of the task, indicating spatial learning and memory impairment compared to the controls. Naloxone administration (1 mg/kg, ip) before each METH injection led to significant attenuations of both hyperthermia and METH adverse effects on the rat performance in the MWM task. Conclusion: The results revealed that pretreatment with the opiate antagonist naloxone could prevent METH adverse effects on body temperature and memory performance. It seems that the opioidergic system and hyperthermia may, at least partially, be involved in METH effects on spatial memory. [GMJ. 2019;8:e1182]